2021
DOI: 10.1101/2021.09.15.460321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic behavior of cell-free mitochondrial DNA in human saliva

Abstract: Mitochondria release their genome as cell-free mitochondrial DNA (cf-mtDNA) in multiple biofluids including in the blood, where it predicts mortality and is a marker of mental and physical stress. Here we report cf-mtDNA in human saliva, an accessible biofluid used to study dynamic neuroendocrine changes. To map the natural dynamics of salivary cf-mtDNA over time, we examine cf-mtDNA and steroid hormones in a small cohort of healthy adults, and perform an intensive repeated-measures analysis of two healthy men… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
1
1
Order By: Relevance
“…Thus, for most biofluids except EDTA plasma, MitoQuicLy should detect sample-to-sample differences in cf-mtDNA concentrations of >10-15%. This sensitivity threshold lies below previously reported basal inter-individual differences in our data (see Figure 6) and by other laboratories (Lindqvist et al, 2016; Lindqvist et al, 2018; Nakahira et al, 2013; Rosa et al, 2020), and also below the magnitude of previously reported within-person changes in cf-mtDNA over time in blood and saliva (Cushen et al, 2020; Hummel et al, 2018; Trumpff et al, 2019; Trumpff et al, 2022). We detected no effect of well position on the 96-well lysis plate, ruling out sample location as a potential contributor to variability.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Thus, for most biofluids except EDTA plasma, MitoQuicLy should detect sample-to-sample differences in cf-mtDNA concentrations of >10-15%. This sensitivity threshold lies below previously reported basal inter-individual differences in our data (see Figure 6) and by other laboratories (Lindqvist et al, 2016; Lindqvist et al, 2018; Nakahira et al, 2013; Rosa et al, 2020), and also below the magnitude of previously reported within-person changes in cf-mtDNA over time in blood and saliva (Cushen et al, 2020; Hummel et al, 2018; Trumpff et al, 2019; Trumpff et al, 2022). We detected no effect of well position on the 96-well lysis plate, ruling out sample location as a potential contributor to variability.…”
Section: Resultscontrasting
confidence: 70%
“…For instance, plasma cf-mtDNA levels may increase over decades with human aging (Pinti et al, 2014), blood cf-mtDNA levels changes over weeks to months during pregnancy (serum) (Cushen et al, 2020), with exercise training (serum) (Nasi et al, 2016), and following psychotropic treatment (plasma) (Lindqvist et al, 2018). Moreover, over much shorter time scales, studies in plasma (Hummel et al, 2018; Lindqvist et al, 2016; Shockett et al, 2016; Stawski et al, 2017), serum (Trumpff et al, 2019), and saliva (Trumpff et al, 2022) show that cf-mtDNA concentrations change several-fold over periods ranging from minutes to hours (reviewed in (Trumpff et al, 2021)), calling for longitudinal and prospective studies with repeated measures to accurately capture cf-mtDNA dynamics. Thus, the need to examine cf-mtDNA across varying timescales and broadly representative participant populations (Clayton and Collins, 2014) calls for studies with large sample sizes, compounding the need for high-throughput, cost-effective, scalable laboratory methods.…”
Section: Introductionmentioning
confidence: 99%